Mental Health Claims Management and Return to Work: Qualitative Insights from Melbourne, Australia - Brijnath, Bianca; Mazza, D.; Singh, N.; Kosny, A.; Ruseckaite, R.; Collie, A. (Springer, 2014)
Purpose Mental health conditions (MHC) are an increasing reason for claiming injury compensation in Australia; however little is known about how these claims are managed by different gatekeepers to injury entitlements. This study, drawing on the views of four stakeholders-general practitioners (GPs), injured persons, employers and compensation agents, aims to describe current management of MHC claims and to identify the current barriers to return to work (RTW) for injured persons with a MHC claim and/or mental illness. Methods Ninety-three in-depth interviews were undertaken with GPs, compensation agents, employers and injured persons. Data were collected in Melbourne, Australia. Thematic techniques were used to analyse data. Results MHC claims were complex to manage because of initial assessment and diagnostic difficulties related to the invisibility of the injury, conflicting medical opinions and the stigma associated with making a MHC claim. Mental illness also developed as a secondary issue in the recovery process. These factors made MHC difficult to manage and impeded timely RTW. Conclusions It is necessary to undertake further research (e.g. guideline development) to improve current practice in order to enable those with MHC claims to make a timely RTW. Further education and training interventions (e.g. on diagnosis and management of MHC) are also needed to enable GPs, employers and compensation agents to better assess and manage MHC claims.